Anastomotic leak after transanal total mesorectal excision: grading of severity and management aimed at preservation of the anastomosis. (18th May 2019) - Guel‐Klein, S.; Biebl, M.; Knoll, B.; Dittrich, L.; Weiß, S.; Pratschke, J.; Aigner, F.
Abstract: Aim: The transanal approach to total mesorectal excision (TaTME) as an alternative to conventional anterior resection offers an improved view to otherwise restricted anatomical regions in obese and narrow male pelves and unfavourable tumour locations. Guidelines for the management of anastomotic leakage (AL) following low rectal resections are scarce. Patients and methods: Prospectively collected data of all consecutive patients undergoing TaTME between December 2014 and April 2017 in our centre were analysed retrospectively. Existing classification systems for AL were modified with regard to transanal anastomotic‐preserving management. Results: TaTME was performed in 66 patients with a median age of 56.2 years. The overall incidence of AL was 12.1% ( n = 8). AL grading was differentiated in Grades I to V according to the severity of necrosis and abscess development. Two patients suffered from AL Grade II, one patient from Grade III, three patients from Grade IV and two patients from Grade V. Preservation of the anastomosis following AL was achieved by the damage control concept in six of eight patients (75%) with a median duration of hospital stay of 36 days. Two patients received a Hartmann procedure (Grades IV and V). Conclusion: Our study demonstrates that management of AL following TaTME is challenging but definitely amenable to strategies aimed at preserving the anastomosis by appropriate damage control. The modified classification system might serve as guidance for anastomosis‐preserving management.